The Influence of Tilia tomentosa Moench on Plant Species Diversity and Composition in Mesophilic Forests of Western Romania–A Potential Tree Species for Warming Forests in Central Europe? - Heinrichs, Steffi; Öder, Veronika; Indreica, Adrian; Bergmeier, Erwin; Leuschner, Christoph; Walentowski, Helge (MDPI AG, 2021)
Climate change challenges important native timber species in Central Europe. The introduction of non-native tree species originating from warmer climates is one option to make Central European forests compatible to global warming. This, however, requires an assessment of the species’ growth requirements, and of its impact on biodiversity in its native ranges. Silver lime (Tilia tomentosa), a moderately drought-tolerant, thermophilous tree species of South-eastern Europe is considered suitable for the future. Along three elevational transects in western Romania, we assessed the impact of changing climate and local site conditions on the abundance of this tree species and contrasted plant species diversity and composition of lime-dominated forests with mesophytic oak and beech forests. Local site conditions and disturbance histories shaped the distribution pattern of silver lime. When dominant, it reduced plant species diversity within stands due to its dense canopy. For shade-tolerant, mesophytic species, though, lime forests provided an additional habitat and extended their range into warmer environments. Thus, silver lime may have the potential as an admixed tree species forming a transitory meso-thermophilous habitat in the future. At the same time, silver lime may be limited under increasing drought frequency.
Keywords: assisted migration; climate change; non-native tree species; habitat function; lime forests; oak forests; complementarity; gamma diversity; European beech forests; elevational gradient